Pengelolaan Laboratorium Microteaching Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Bengkulu - Yolanda, Desty; Somantri , Manap (UNIVERSITAS BENGKULU, 2024)
The purpose of this research is to analyze the management of the microteaching laboratory, including planning, implementation, evaluation, and follow-up at the Faculty of Educational Sciences, Muhammadiyah University of Bengkulu. The method used is qualitative research. Qualitative research is an approach aimed at understanding phenomena by deeply and comprehensively gathering information through interviews, observations, or document analysis.The research findings indicate that the planning has been carried out effectively by the microteaching laboratory's management. However, it is not yet optimal due to the limitation imposed by the fact that the laboratory is also managed by the faculty. The implementation has been done well, although there are some shortcomings, such as budget constraints. The evaluation has been performed reasonably well but not maximally because it only evaluates specific issues rather than the entire process. The follow-up actions are generally adequate, although there is room for improvement since not all issues receive follow-up actions after evaluation. In summary, the research highlights both strengths and areas for improvement in the management of the microteaching laboratory at the Faculty of Educational Sciences, and it suggests that optimizing the planning and evaluation processes, as well as ensuring consistent follow-up, could lead to better overall management of the laboratory.